EFFECT OF INTERNET BANKING AND MOBILE BANKING USAGE ON SHARE PRICES THROUGH INDONESIAN BANKING FINANCIAL PERFORMANCE REGISTERED ON THE INDONESIA STOCK EXCHANGE - Angella Tiosanna; Isfenti Sadalia; Chairul Muluk (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
The purpose of this study was to analyze the effect of the use of internet banking and mobile banking on stock prices through the financial performance of Indonesian banks. The population in this study are banking sector companies listed on the Indonesia Stock Exchange. The number of samples in this study was 7 with criteria determined by the researcher. The data analysis technique used is descriptive analysis and multiple linear regression analysis. The results of this study indicate that the internet banking variable has a positive and insignificant effect on stock prices, the mobile banking variable has a negative and significant effect on stock prices and the financial performance variable has a positive and insignificant effect on stock prices.